The Death of the Self: Novels by Ondaatje and Marlatt - Murdock, Rebecca Mary (My University, 1990)
Using similar disjunctive writing styles, Michael Ondaatje and Daphne Marlatt create characters who defy stability, consistency, and predictability. Both authors undermine the notion that the self is a unified entity determined to resist an ambiguity in the search for univocal meaning. Rather, the worlds inhabited by Buddy Bolden, Lalla Dickman, Mervyn Ondaatje, and Ina as found in Coming Through Slaughter, Running in the Family, and Ana Historic subscribe to uniformity by valourizing social and textual conventions. Within these contexts of closure, all characters succumb to some degree of hysteria, madness, or death. In Ondaatje's novels scandal becomes a release from the monotony of a unified self, while in Ana Historic Annie Anderson's continual displacement of pronouns effectively suspends female identity. Ondaatje and Marlett fictionalize the post-structuralist work of Roland Barthes in "The Death of the Author" in that both authors create characters whose boundaries are never fixed, but always shifting according to the contexts in which they find themselves. On this basis the self as embodied in the pronoun "I" contains not a set persona, but a network of competing voices. In the final chapter of this thesis, I examine the implications for authorship which Ondaatje and Marlatt raise in their contention that the self exists without a central core. During moments of autobiography, Ondaatje and Marlatt implicitly contest the defacement of their signatures on novels which call for an obfuscation of identity, but arrest that movement when it folds back on the author's domain--the outer cover of the text. Because Ondaatje and Marlett elide themselves with their characters, they, too, are pulled into a vertigo of language that knows not identity, but the endless positing and erasure of tropes.
Keywords: Michael Ondaatje, Daphne Marlatt, characters, stability, consistency, predictability, ambiguity, monotony, identity